Tendencje rozwojowe w systemach wynagrodzeń firm globalnych - Kawka, Tomasz (New trends of compensation systems in global firms, 2006)
The paper describes a development tendency related to compensation systems in the specific kind of organizations - global, multinational firms. New trends in personal functions are the result of perception’s change from a local view into the global view. This is a result of economy globalization and rapid increase of the number of multinational firms. A new era is arising called new economy era. One of the most difficult questions in contemporary process of management is how to solve problems connected with international and culture conditions. Compensation systems concentrate all these issues, and to create and administrate such a system is, as we can say, to tame “Babel Tower”. In the face of globalization there is a change of role of pay as a tool of strategic management. It is perceived as feedback with organization culture. There is an increase of importance of pro-competitive meaning of compensation system. That system should be aimed at flexibility and connected with competence. In the end, there are problems connected with inequality of levels of pay, and questions with problems of repatriation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 221-232